Rethinking Urban Resilience: A Bottom-Up Approach to Public Space Management in Bogotá, Colombia - Mora, Javier; Garavito, Milton (MAJ - Malaysia Architectural Journal, 2025)
The escalating climate crisis demands innovative solutions for urban adaptation. This paper argues for a bottom-up approach, centered on the active participation of architects, communities, and end users in redesigning and managing public spaces. This shift is imperative to achieve the objectives of the Sustainable Development Goals, particularly SDG 16.7 on inclusive and participatory decision-making. The document examines the case study of Locality 11 Suba-La Gaitana, in Bogotá, Colombia, where facing growing informality and public space misuse the local government through an effective governance (economy) implemented tactical urbanism practices (urban design). Efforts with and for the community contributed to normalization of public spaces dedicated to their economic activities. The normalization led to formal agreements between the vendors and the local administration, which established regulations and segmented spaces for product display. Moreover, vendors received identification, training in financial education and business management, and access to support programs through the Network Services program. Through a polycentric approach, informal vendors were formally integrated into the local economy, contributing to increased tax revenue and improved public order. The model also fostered a sense of ownership and responsibility among community members towards their public spaces. The "Portal de Suba", another replicated initiative involving the local government, street vendor organizations, and the Institute for the Social Economy, further highlights the scalability and replicability of this model. The paper describes how the Suba-La Gaitana case and its broader implications can be applied to not only other Colombian and Latin American cities, but also to other third world cities with an informal economy and public space misuse. It contributes to the discourse on sustainable urban development and proposes a participatory approach as a strategy for building resilient and inclusive cities in the face of climate change.